If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 + 2x + 4 + x + 10 = o Reorder the terms: -2 + 4 + 10 + 3x + 2x + x = o Combine like terms: -2 + 4 = 2 2 + 10 + 3x + 2x + x = o Combine like terms: 2 + 10 = 12 12 + 3x + 2x + x = o Combine like terms: 3x + 2x = 5x 12 + 5x + x = o Combine like terms: 5x + x = 6x 12 + 6x = o Solving 12 + 6x = o Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 6x = -12 + o Combine like terms: 12 + -12 = 0 0 + 6x = -12 + o 6x = -12 + o Divide each side by '6'. x = -2 + 0.1666666667o Simplifying x = -2 + 0.1666666667o
| -61=12a-1 | | 3x^2+3y^2=6 | | 53=5-2u | | 1-8k-9k-4= | | 29-4x=4 | | 2y+9fory=-6 | | 6f-7f-1=-5-5f | | 3a+a+25=225 | | 2+2x-5=5x+3 | | x+7+3x-1+2x+5=0 | | 5-y=-2x-5 | | X=32+2x | | 4x*1=0 | | -q=8+q | | 23x^2+50x+25=0 | | 2x+(x+1)=4 | | m^3+4=1 | | 2x+x+1=4 | | 0.2f=-8.4 | | -12(2-t)=14t | | 4v+10+v-9= | | x+6(4)=29 | | (2d-7)=(2+4d)2 | | a+.75a=21 | | 0=2x^2+1x-6 | | 3x+17+3+7x=x | | 2(-6y+29)-4y=-6 | | (2(23)+21)= | | y,5-6=8 | | 3+n^3=6 | | 90+x+(2x+21)=180 | | 5u-37=2(u+1) |